Monetary Policy Rates and Dividend Policy of Deposit Money Banks in Nigeria: A Dynamic Fixed Effects Approach - James Agbekeme Sarakiri (Research Parks Publishers, 2021)
This paper investigates the effects of monetary policy on dividend payout decisions of deposit money banks in Nigeria using the dynamic fixed effects model. The study covers from 2010 to 2019 and is based on a sample of listed banks in Nigeria. While dividend policy is proxied by dividend per share and dividend payout ratio, four monetary policy variables are examined: namely, monetary policy rate, treasury bills rate, interbank call rate and open buy back rate. We find that unobserved firm-specific factors are significant determinants of both dividend payout and dividend payout ratio. Our results also show that while none of the policy rates has a significant impact on dividend per share, only monetary policy rate is significantly related to dividend payout ratio. However, the impact of interbank call rate on dividend per share is significant at 10% level. We interpret the significance of monetary policy rate, whose coefficient is negatively signed, as suggesting that restrictive monetary policy increases both the cost of raising funds and the level of asymmetric information in the credit market, thereby forcing managers of these banks to reduce their payout ratio, which also has implication for corporate financing decisions.